The "Kite-t-FAMMIF": A Novel Technique for Reconstruction of Extensive Soft Palate Resection. Issue 10 (17th October 2022) - Massarelli, Olindo; Carnevale, Claudio
Abstract : Summary: Total soft palate reconstruction is a challenge for the head and neck surgeon. Velopharyngeal incompetence resulting from soft palate resection impairs both speech and swallowing and significantly affects the quality of life of the patients. Radial forearm free flap is the reconstructive technique most used worldwide, but it requires microsurgical skills, is associated with high donor site morbidity, and shrinks during the healing process, especially after adjuvant radiotherapy. We present a novel technique using a single "kite-shaped" tunnelized-facial artery myomucosal island flap (t-FAMMIF) and report very favorable functional outcomes. Three patients in whom a kite-shaped flap was used to reconstruct a total soft palate defect after squamous cell carcinoma resection were included. In two of them, the resection included both tonsils due to cancer spreading to the tonsillar fossae. The mucosal and muscular sides of a single t-FAMMIF flap were able to restore the oral and nasal lining of the palate, respectively, without the need to fold the flap. All patients were able to tolerate an oral soft diet 10 days after surgery. No complications were detected. A complete mucosalization on the nasal lining was observed by video-endoscopy 3 weeks after surgery. No case of shrinking of the flap was observed during the follow-up, and speech and swallowing functions were not impaired after complete wound healing. Kite-shaped t-FAMMIF represents an excellent and feasible reconstructive option for extensive postablative soft palate defects.